RECALIBRATION OF MUTUALLY CONSISTENT GARNET-BIOTITE AND GARNET-CORDIERITE GEOTHERMOMETERS - Kaneko Y.; Miyano T. (My University, 2004)
Garnet–biotite and garnet–cordierite geothermometers have been consistently calibrated, using the results of Fe2+–Mg cation exchange experiments and utilizing recently evaluated nonideal mixing properties of garnet. Nonideal mixing parameters of biotite (including Fe, Mg, AlVI, and Ti) and of cordierite (involving Fe and Mg) are evaluated in terms of iterative multiple least-square regressions of the experimental results. Assuming the presence of ferric Fe in biotite in relation to the coexisting Fe-oxide phases (Case A), and assuming the absence of ferric Fe in biotite (Case B), two formulae of garnet–biotite thermometer have been derived. The garnet–cordierite geothermometer was constructed using Margules parameters of garnet adopted in the garnet–biotite geothermometers. The newly calibrated garnet–biotite and garnet–cordierite thermometers clearly show improved conformity in the calculated temperatures. The thermometers give temperatures that are consistent with each other using natural garnet–biotite–cordierite assemblages within ±50 °C. The effects of ferric Fe in biotite on garnet–biotite thermometry have been evaluated comparing the two calibrations of the thermometer. The effects are significant; it is clarified that taking ferric Fe content in biotite into account leads to less dispersion of thermometric results.
Keywords: Geothermometry; Garnet; Biotite; Cordierite; Ferric iron; Regression analysis